Analisis Konten HOTS dalam Buku Siswa Kelas V Tema 6 “Panas dan Perpindahannya” Kurikulum 2013 - Arif Widodo; Dyah Indraswati; Radiusman Radiusman; Umar Umar; Nursaptini Nursaptini (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this study is to analyze the content or problems presented in a student's book in accordance with the criteria as teaching materials with high-level skills in elementary school. The study uses content analysis methods with stages of data reduction, data presentation and conclusion drawing. Data collection is done by rubrics then presented in graphical form. The data source in this study is the 2013 thematic integrated curriculum book for elementary / MI class V theme 6